2005
DOI: 10.1182/blood-2004-04-1450
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ plays opposite roles in growth mediated by wild-type Kit and an oncogenic Kit mutant

Abstract: IntroductionKit, the receptor for stem cell factor (SCF), is a type III receptor tyrosine kinase of the platelet-derived growth factor (PDGF) subfamily. c-kit maps to the white spotting (W) locus in the mouse, 1,2 while the gene for its ligand SCF maps to the steel (Sl) locus. 3,4 Mutations that reduce function or expression of either the receptor or ligand lead to macrocytic anemia, mast cell deficiency, abnormal pigmentation of skin and hair, infertility, reduced gastrointestinal motility, and impaired hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
14
1
Order By: Relevance
“…This is in contrast to another report [24] that suggested a differentiating but not transforming potential for the mutation, which nevertheless probably participates in enhancing mast cell chemotaxis [25] and clustering [26]. Mutant Kit signaling might involve both PI3K [27] and Src [28] participation although utilization of pathway molecules might be different between the wild-type and mutant protein [29]. …”
Section: Mastocytosis-relevant Kit Mutationscontrasting
confidence: 51%
“…This is in contrast to another report [24] that suggested a differentiating but not transforming potential for the mutation, which nevertheless probably participates in enhancing mast cell chemotaxis [25] and clustering [26]. Mutant Kit signaling might involve both PI3K [27] and Src [28] participation although utilization of pathway molecules might be different between the wild-type and mutant protein [29]. …”
Section: Mastocytosis-relevant Kit Mutationscontrasting
confidence: 51%
“…This mutant is also found in germ cell tumors (9 -11) and in acute myeloid leukemias (7,8). Previous studies have reported the activation of STAT1 or STAT3 by KIT-D816V in transfected cell lines (18,30,44); however, very few have addressed the activation of STAT in neoplastic cells. A noticeable exception is a recent description of STAT5 activation and STAT5 requirement for cell proliferation in HMC-1 cells (19).…”
Section: Discussionmentioning
confidence: 97%
“…53 Using chemical inhibitors, it has been suggested that NF-B, mTOR, and PKC␦ are important effectors of KIT D816V . [54][55][56] These hypotheses have not yet been challenged using gene inactivation techniques. Using antisense oligonucleotides and RNA interference, another study very recently implicated the BCL-2-related protein MCL-1 in KIT D816V -dependent cell proliferation.…”
Section: Signaling Downstream Of Kit D816vmentioning
confidence: 99%
“…on May 11, 2018. by guest www.bloodjournal.org From PKC412, 60,63,64 and drugs that target NF-B, 54 mTOR, 56 protein kinase C ␦ (PKC␦), 55 PI3K, 52 and heat shock protein 90 (HSP90). 65 The present study points to FES as a putative target of KIT D816V -mediated cell proliferation.…”
Section: Inhibitors Of Kit D816vmentioning
confidence: 99%